Return on NFTs - Franceschet, Massimo; Della Libera, Davide (Frontiers in Blockchain, 2023)
Currently, the best known applications of blockchain technology are finance and art. In particular, the blockchain art market, born in early 2018 without fuss, went parabolic around 2021, also thanks to record-breaking sales of digital artworks associated with a Non-Fungible Token (NFT), mediated by the grand dames of auction houses Christie's and Sotheby's. In this contribution we merge art and finance on blockchain and explore the opportunity of buying blockchain art as a financial investment. While there exists a relatively large literature on traditional art as investment, the topic of investing in NFTs is still in its infancy. Thus, we provide methods (metrics) and tools (a Web app) to reason about opportunities, in terms of risks and returns, of investing in art on chain.